2018
DOI: 10.3989/gya.0664171
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation kinetics of hazelnut oil treated with ozone

Abstract: SUMMARY:The present study investigates the oxidation kinetics of hazelnut oil ozonated in different treatment periods (1, 5, 60 and 180 min). The kinetic rate constant (k) was taken as the inverse of oxidation onset time (T o ) observing a linear relationship from the plot of lnT o to isothermal temperatures (373, 383, 393, and 403 K) carried out at differential scanning calorimetry. Kinetic parameters, activation energy (E a ), activation enthalpy (ΔH ‡ ) and entropy (ΔS ‡ ) were calculated based on the Arrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…The results with respect to PV are in accordance with the observations of other authors for ozonated pistachios and whole wheat flour (Babaee et al, 2022). Ozone treatment was observed to increase the PV of hazelnut oil samples exponentially, according to Uzun and Ibanoglu (2017). Additionally, Chen et al (2014) and de Oliveria et al (2020) observed an increase in the peroxide index of oils extracted from ozonized peanuts and Brazil nuts, respectively.…”
Section: Effect Of Ozone Treatment Of Hazelnuts On Peroxide Value (Pv...supporting
confidence: 90%
“…The results with respect to PV are in accordance with the observations of other authors for ozonated pistachios and whole wheat flour (Babaee et al, 2022). Ozone treatment was observed to increase the PV of hazelnut oil samples exponentially, according to Uzun and Ibanoglu (2017). Additionally, Chen et al (2014) and de Oliveria et al (2020) observed an increase in the peroxide index of oils extracted from ozonized peanuts and Brazil nuts, respectively.…”
Section: Effect Of Ozone Treatment Of Hazelnuts On Peroxide Value (Pv...supporting
confidence: 90%
“…The PV of hazelnut are used as an indicator of the level to which F I G U R E 1 Effect of ozonation on the degradation of aflatoxin B1 and total aflatoxins in hazelnut kernels oxidative rancidity reactions reached during ozonation. Hazelnut is rich in monounsaturated (MUFA) and polyunsaturated (PUFA) (approximately 83% MUFA and 9% PUFA) fatty acids even though it has been reported to have high oxidative stability due to its high α-tocopherol content (Uzun & Ibanoglu, 2017).…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…The activation energy (E a ) of 105000.3 J mol −1 and the rate constant (k) of 2.6 × 10 −4 min −1 were estimated by nonlinear regression, also considering the Arrhenius law. The enthalpy of activation (∆H) of 9.81 x 104 J kg −1 was obtained by linear regression, according to the activation complex theory (Uzun & Ibanoglu, 2018). The parameters were then applied to the continuous version of the kinetic treatment, as seen in Table 1 of the following item 2.5.…”
Section: Apparent Kinetic and Thermodynamic Parametersmentioning
confidence: 99%